2017
DOI: 10.1080/19390211.2017.1346031
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Virgin Coconut Oil Improves Lipid Profile and Hepatic Antioxidant Status and Has Potential Benefits on Cardiovascular Risk Indices in Normal Rats

Abstract: Research findings that suggest beneficial health effects of dietary supplementation with virgin coconut oil (VCO) are limited in the published literature. This study investigated the in vivo effects of a 5-week VCO-supplemented diet on lipid profile, hepatic antioxidant status, hepatorenal function, and cardiovascular risk indices in normal rats. Rats were randomly divided into 3 groups: 1 control and 2 treatment groups (10% and 15% VCO-supplemented diets) for 5 weeks. Serum and homogenate samples were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 32 publications
1
18
1
1
Order By: Relevance
“…Rabeh and El-Ghandour (2016) and Aisuodionoe et al (2018) reported that VCO improves metabolic parameters, antioxidant enzyme activities, reduces oxidative stress and lipid peroxidation in diabetes. Famurewa et al (2018) mentioned that beneficial effects of VCO on lipid profile, antioxidant hepatic defense system, and cardiovascular risk indices in rats. Hamza (2010) revealed that treatment with moringa seed extract can significantly reduce the indices of hepatotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabeh and El-Ghandour (2016) and Aisuodionoe et al (2018) reported that VCO improves metabolic parameters, antioxidant enzyme activities, reduces oxidative stress and lipid peroxidation in diabetes. Famurewa et al (2018) mentioned that beneficial effects of VCO on lipid profile, antioxidant hepatic defense system, and cardiovascular risk indices in rats. Hamza (2010) revealed that treatment with moringa seed extract can significantly reduce the indices of hepatotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Iranloye et al (2013) suggested that VCO reduces oxidative stress by boosting the antioxidant defense system, scavenging free radicals and reducing lipid peroxidation; another independent study suggested that fresh coconut oil can reduce oxidative stress associated with diabetes mellitus. Famurewa et al (2018) showed that VCO decreased malondialdehyde (MDA) levels, and increased activities of hepatic antioxidant enzymes superoxide dismutase (SOD). Virgin coconut oil contains high unsaponifiable lipid components like vitamin E and polyphenols, tocotrienols, tocopherols, ÎČ carotene and phytosterol in stabilising cell membranes by preventing alterations in membrane lipid polarity and fluidity (Jaarin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…17 The use of coconut oil is promoted by the media for weight loss, improvement of lipid profile, and others health effects, but most studies evaluated the effects of this oil associated with a normal diet. [18][19][20][21] Considering the negative effects of a high-fat diet (HFD) and the recent recommendations on the consumption of SFA, we investigate the effects of VCO associated with HFD on biochemical, inflammatory, and oxidative stress parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in increased interest in utilizing the beneficial potentials of natural products with antioxidant properties to quench or break free radical chain. A growing body of evidence shows that VCO or MOO possesses antioxidant and pharmacological activities (Abarikwu, Benjamin, Ebah, Obilor, & Agbam, ; Famurewa et al, ). A recent investigation demonstrates that oral supplementation of VCO enhances memory and neuronal mechanisms and modulates oxidative stress in Wistar rats (Rahim, Lim, Mani, Majeed, & Ramasamy, ).…”
Section: Introductionmentioning
confidence: 99%